Validação de método por cromatografia líquida em fase reversa para avaliação de potência de molgramostima. Correlação com o bioensaio - Leal, Diogo Paim (2010)
The granulocyte-macrophage colony stimulating factor (GM-CSF) is a cytokine that regulates the proliferation and differentiation of hematopoietic progenitor cells and activates mature granulocytes and macrophages. Clinically is used in enhancing hematopoietic recovery after cancer chemotherapy and bone marrow transplantation. A reversed-phase liquid chromatography (RP-LC) method was validated for the determination of the non-glycosylated recombinant rhGM-CSF (Molgramostim) in biopharmaceutical formulations. The RP-LC method was carried out on a Jupiter C4 column (250 mm x 4.6 mm i.d.), maintained at 45 ºC. The mobile phase A consisted of 0.1% TFA and the mobile phase B consisted of 0.1% TFA in acetonitrile, run at a gradient from: 0.01 34 min, 37% 50% of B; 34 35 min linear back to 37% of B and 35 40 min, 37% of B. The flow rate was 1 mL/min, and using photodiode array (PDA) detection at 214 nm. The chromatographic separation was obtained with the retention time of 29.2 min, and was linear over the concentration range of 2-300 μg/mL (r2 = 0.9992). The procedure was validated evaluating parameters such as the specificity, linearity, precision, accuracy, robustness, limit of detection and limit of quantitation. The specificity was proven through degradation studies, showing that also there was no interference of the excipients. Moreover, the in vitro cytotoxicity test of the degraded products showed significant differences (p<0.05). The proposed method was applied for the analysis of molgramostim and their related proteins, and the results were correlated to the bioassay, showing mean differences of the potency 1.02% higher for the RP-LC method, contributing to establish alternatives to characterize and monitoring its instability, improving the quality control and assuring the therapeutic efficacy.